2017
DOI: 10.5194/bg-14-2815-2017
|View full text |Cite
|
Sign up to set email alerts
|

Increased temperature causes different carbon and nitrogen processing patterns in two common intertidal foraminifera (<i>Ammonia tepida</i> and <i>Haynesina germanica</i>)

Abstract: Abstract. Benthic foraminifera are highly abundant heterotrophic protists in marine sediments, but future environmental changes will challenge the tolerance limits of intertidal species. Metabolic rates and physiological processes in foraminifera are strongly dependent on environmental temperatures. Temperature-related stress could therefore impact foraminiferal food source processing efficiency and might result in altered nutrient fluxes through the intertidal food web. In this study, we performed a laborator… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 95 publications
(115 reference statements)
4
26
0
Order By: Relevance
“…There is not much known about foraminiferal nitrogen regeneration from organic matter, but isotope tracer studies in the Arabian Sea have shown a high contribution to the processing of phytodetrital nitrogen by benthic foraminifera ( Enge et al, 2016 ). Feeding experiments with A. tepida have also shown a coupling of carbon and nitrogen intake from D. tertiolecta detritus ( Wukovits et al, 2017 ), which is also apparent in the present study (see ).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…There is not much known about foraminiferal nitrogen regeneration from organic matter, but isotope tracer studies in the Arabian Sea have shown a high contribution to the processing of phytodetrital nitrogen by benthic foraminifera ( Enge et al, 2016 ). Feeding experiments with A. tepida have also shown a coupling of carbon and nitrogen intake from D. tertiolecta detritus ( Wukovits et al, 2017 ), which is also apparent in the present study (see ).…”
Section: Discussionsupporting
confidence: 85%
“…Thermal response curves revealed a steep rise of oxygen consumption in A. tepida between 20°C and 30°C ( Bradshaw, 1961 ) and in respiration of A. tepida which was substantially higher at 23°C compared to 7°C ( Cesbron et al, 2016 ). This effect of temperature has also been observed on the level of carbon processing in A. tepida in a former feeding experiment ( Wukovits et al, 2017 ). There, a single low food pulse (∼220 µg C m −2 ) at three different temperatures (20°C, 25°C, 30°C) resulted in the highest levels of pC in A. tepida at 25°C.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations